2016
DOI: 10.1002/star.201500333
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical properties of a novel pullulanase of Paenibacillus lautus DSM 3035

Abstract: The pullulanase gene (pul PL ), encoding a novel type I pullulanase (Pul PL ), was obtained from a Paenibacillus lautus DSM3035 isolate. The gene has an open reading frame of 2355 bp, After optimizing induction conditions in Escherichia coli, we overexpressed recombinant Pul PL , purified this enzyme, and assayed its function . The level of functional Pul PL -like protein reached its maximum (about 0.28 mg/mL, 15% of total protein) after induction for 16 h at 20°C. Under these optimized harvesting conditions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…Using molecular technique, subunit molecular weight of the purified pullulanase (Pull) was estimated to be 42.34 kDa. The molecular mass obtained in this study is found to be lower than that of Paenibacillus lautus , 87.9 kDa ( Chen et al., 2016 ). Much higher molecular weight was observed for pullulanase of Klebsiella pneumonia (94 kDa) ( Abdul-Hadi and Al-Bayyar, 2019 ), Bacillus acidopullulyticus (102 kDa) ( Lappalainen et al., 1991 ), Pyrobaculum calidonfontis (111 kDa) ( Rehman et al., 2018 ), white edible mushroom (112 kDa) ( Shehata et al., 2016 ), Bacillus sp (136 kDa) ( Orhan et al., 2014 ).…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…Using molecular technique, subunit molecular weight of the purified pullulanase (Pull) was estimated to be 42.34 kDa. The molecular mass obtained in this study is found to be lower than that of Paenibacillus lautus , 87.9 kDa ( Chen et al., 2016 ). Much higher molecular weight was observed for pullulanase of Klebsiella pneumonia (94 kDa) ( Abdul-Hadi and Al-Bayyar, 2019 ), Bacillus acidopullulyticus (102 kDa) ( Lappalainen et al., 1991 ), Pyrobaculum calidonfontis (111 kDa) ( Rehman et al., 2018 ), white edible mushroom (112 kDa) ( Shehata et al., 2016 ), Bacillus sp (136 kDa) ( Orhan et al., 2014 ).…”
Section: Discussioncontrasting
confidence: 58%
“…The optimum pH 7.0 exhibited by B. safensis pullulanase isolated from the gut of termite is consistent with Paenibacillus lautus pullulanase ( Chen et al., 2016 ), and B. subtilis and Geobacillus thermoleovorans NP 33 pullulanase ( Nisha and Satyanarayana, 2018 ). Significantly, the enzyme exhibited high relative activity of 91 and 94, respectively at acidic pH 5.0 and 6.0 respectively.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The previous articles described the methods for heterologous protein expression and Ni‐NTA purification procedures in our group . Pullulanase activity of Pul GK was measured in triplicate spectrophotometrically at 65 °C using the 3,5‐dinitrosalicylic acid (DNS) method .…”
Section: Methodsmentioning
confidence: 99%